2010
DOI: 10.1108/17539261011094704
|View full text |Cite
|
Sign up to set email alerts
|

Public REITs' governance and regulatory structure: effects on NAV discount

Abstract: PurposeThe purpose of this paper is to investigate the influence of the Italian real estate investment trusts (REITs)' governance and regulatory structure on the market prices discount to net asset values (NAV).Design/methodology/approachThe hypothesis is that the overall regulatory design and the rules for prudential vigilance (i.e. governance rights, closed‐end form, leverage constraints, and mandatory listing) influence REITs' share value, both as market price and as NAV). In particular, the analysis focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Further systematic factor which are not explicitly analyzed in this study include regulation (Biasin et al, 2010) and short sales constraints (Brounen et al, 2013).…”
Section: Hypothesis 4: Nav Spreads Of Reocs and Reits Increase With Imentioning
confidence: 99%
“…Further systematic factor which are not explicitly analyzed in this study include regulation (Biasin et al, 2010) and short sales constraints (Brounen et al, 2013).…”
Section: Hypothesis 4: Nav Spreads Of Reocs and Reits Increase With Imentioning
confidence: 99%
“…Besides that, a study conducted by Biasin et al (2010) revealed that the NAV discount is negatively affected by the share turnover and leverage of Italian REIT. Besides that, a study conducted by Biasin et al (2010) revealed that the NAV discount is negatively affected by the share turnover and leverage of Italian REIT.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following a financial valuation perspective, the effects on (public) share prices of leveraging are uncertain and depend on which capital structure theory best explains the peculiar institutional and regulatory framework of (European) REITs generally characterized, below other, by a corporate tax free context ( (Biasin, Giacomini, & Quaranta, 2010;Feng, Ghosh, & Sirmans, 2007).…”
Section: The Effects On Share Value and Performance For Gav And Nav-bmentioning
confidence: 99%